Experimental investigation of peculiarities for impact of a sorption action preparation silicon dioxide on infectious agents of cholangitis - O. I. Dronov; I. O. Kovalska; I. L. Nastashenko; T. O. Kondratiuk; L. V. Levchenko (Клінічна хірургія, 2021)
Objective. Determination of impact of combination, consisted of 3% solution of silicon dioxide and antibacterial preparations, on bacterial cultures of S. aureus, P. aeruginosa, E. coli.